Chromogenic mechanisms in blue-and-white porcelains. Issue 15 (December 2020) - Pinto, Ariane; Groenen, Jesse; Zhao, Bing; Zhu, Tiequan; Sciau, Philippe
Abstract: The blue underglaze decorations of Chinese blue-and-white porcelains are due to the use of a cobalt-based blue pigment. Nevertheless, for a same time period and production centre, wares can present wide colour variations in both hue and intensity. Fourteen Ming samples were investigated using colorimetry, Raman spectroscopy and SEM-EDS, in order to better understand the origin of these variations. The majority of the sherds dates back to the middle 15th- early 16th century. The chromogenic mechanism of the hue and intensity variations appears to be complex and multifactorial. Six main factors have been identified: the elemental composition of the pigment particles, in particular the Fe/Co ratio, the pigment spinel structure, the size as well as the distribution of the colouring particles, the environment of the pigment particles and the colour of the glaze.